No higher honor a memoir of my years in Washington - Rice, Condoleezza (New York Crown Publishers, 2011)
From one of the world?s most admired women, this is former National Security Advisor and Secretary of State Condoleezza Rice?s compelling story of eight years serving at the highest levels of government. In her position as America?s chief diplomat, Rice traveled almost continuously around the globe, seeking common ground among sometimes bitter enemies, forging agreement on divisive issues, and compiling a remarkable record of achievement.
Includes index.
Keywords: Rice, Condoleezza, 1954-